تفسير سورة القدر للعالم العلامة و البحر الفهامة ، شمس الدين محمد بن محمد الأمير ت 1232 هـ : دراسة و تحقيق - الأمير، شمس الدين محمد بن محمد، ت. 1232 هـ.; العيثاوى، عماد كريم حمد (ديوان الوقف السني - مركز البحوث والدراسات الاسلامية, 2013)
It is not hiding the importance of the (Al Qadr) in showing the night which the Holy Quran was descended, and the interpreters differed on it , this Sura descended in (Medina) at most ,,and some mentioned it descended in (Mecca) ,it's explination included the meanings , grammar ,and the provisions of that holy night and what other provisions concerned .
Keywords: العلماء المسلمون -- الأمير، محمد بن محمد أحمد ، ت 1232 هـ -- التراجم -- مخطوط تفسير سورة القدر -- تحقيق المخطوطات